Pactical Mapeh 7: teacher's guide - Africa, Antonio P. (Makati City : Diwa Learning Systems, 2018)
The practical mapeh teacher's manual has been developed to enhance the understanding and appreciation of the accompanying practical mapeh textbook. The textbook has been developed to cater to the understanding, interest, potentials and capabilities of different types of learners. It develops college readiness standards ans the 21st century skilld.
English Text.